Plasters of the late chalcolithic 3-4 (3800 - 3400 BCE) from the site of Arslantepe. A contribution to the analysis of archittectural techniques and practices - Alkhasoneh, Samah Jazi Faisal (2020)
ABSTRACT: A multi-analytical approach focus on the archaeometric characterization of plaster from temple C, and two elite houses belong to the late chalcolithic 3-4 (3800-3400 B.C), period VII in Arslantepe – Turkey, a site located in the Malatya plain, 5 km away from the city center and 15 km away from the Euphrates right bank, is done using three different methods: optical microscopy (OM) in thin section under polarizing microscopy to define petrographic features in terms of plaster fabric texture and structure as well as the type, percentage, ratio grain size and distribution of the added aggregate and inclusions Micro-morphological analysis has been carried out by Scanning Electron Microscopy coupled with Energy Dispersive Spectroscopy (SEM-EDS) to define the fabric , inclusions and the secondary product in the pores . a mineralogical analysis by X-ray powder diffraction (XRPD) has been carried out also to identify the quantitative and qualitative mineralogical composition of the samples. In a result a marly limestone has been determine as a plaster raw material which probably came from two different source (local and other imported from different part of Malatya plain). Moreover, different aggregate selection, and diffirent technological levels were also detected in the samples, that are probably related to the level or the purpose (function) of the buildings. An evidence of a re-plastering process was also detected in the two elite houses, which probably refer to a routine maintenance process.